ANGIOFIBROMA OF THE EXTERNAL AUDITORY CANAL: A CLINIC CASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Angiofibromas mostly affect the nasopharynx and account for less than 1% of all head and neck tumors. Rarer are extra-nasopharyngeal angiofibromas. Surprisingly, there has only been one incidence of the external auditory canal being located. We report a case of angiofibroma in this unusual site in a female patient who had hypoacusis and right ear fullness for six months. A mass connected to the posterosuperior wall of the right external auditory canal was discovered during the clinical examination. An average of 37.5 dB of right conductive hearing loss was found during preoperative audiometry. On the left external auditory canal, a mass was discovered using a computed tomography scan. The mass was surgically removed, and the diagnosis was validated by the histological evaluation. Following surgery, audiometry revealed improved hearing. No recurrence occurred.